A Highly Efficient Co3V2O8/MoS2/Carbon Cloth Nanocomposite Bifunctional Electrocatalyst for Overall Water Splitting. Issue 45 (1st December 2020) - Xu, Qixin; Qin, Weiwei; Tian, Wenyu; Chu, Jin‐Feng
Abstract: As a clean energy source, water splitting can produce both hydrogen and oxygen, so it is significant to design high performance bifunctional electrocatalysts to improve the reaction efficiency, but remains a challenge. Herein, a Co3 V2 O8 /MoS2 / carbon cloth (Co3 V2 O8 /MoS2 /CC) composite was prepared by two‐step hydrothermal growth of Co3 V2 O8 /MoS2 on carbon cloth. This nanocomposite exhibited highly efficient electrocatalytic properties in both hydrogen evolution reactions and oxygen evolution reactions. When the current density reached 10 mA cm −2, it merely required the overpotentials of 98 mV and 259 mV, respectively. Moreover, at a two‐electrode system, we measured the performance of Co3 V2 O8 /MoS2 /CC acted as both anode and cathode, and the current density could achieve 10 mA cm −2 with the voltage of only 1.62 V. Abstract : A novel Co3 V2 O8 /MoS2 /carbon cloth nanocomposite was prepared through a two‐step hydrothermal method, which acted as an efficient bifunctional electrocatalyst for overall water splitting and exhibited the good durability. To reach the current density of 10 mA cm −2, this nanocomposite only required the overpotentials of 98 mV and 259 mV for HER and OER, respectively. Its special array structure and the synergy between Co3 V2 O8 and MoS2 could be attributed to the excellent electrochemical performance.